Criminalization and judicialization of environmental defenders: the case of the Crucitas Mining Project, Costa Rica - Alvarado Alcázar, Omar Alejandro (2021)
This article discusses the criminalization of social protest and environmental advocacy in Costa Rica, based on the case study of the struggle against the Crucitas Mining Project (PMC), sustained between 2008 and 2010. The study included a methodology focused on bibliographic and press review and interviews with environmental defenders who faced criminal complaints for their activism against the PMC. In this case, as in other countries in the region, the criminalization and, particularly, the judicialization of the protest, has been a resource used by state and non-state actors to obstruct the work of environmental defenders. Likewise, it has been found that, in the case of the fight against the PMC, the use of the criminal complaint had a triple purpose: to delegitimize, intimidate and inhibit people who fought against mining.